If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 4 + -4X = 12whatisx Reorder the terms: 4 + -4X + 5x = 12whatisx Solving 4 + -4X + 5x = 12ahistwx Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4X + -4 + 5x = -4 + 12ahistwx Reorder the terms: 4 + -4 + -4X + 5x = -4 + 12ahistwx Combine like terms: 4 + -4 = 0 0 + -4X + 5x = -4 + 12ahistwx -4X + 5x = -4 + 12ahistwx Add '-5x' to each side of the equation. -4X + 5x + -5x = -4 + 12ahistwx + -5x Combine like terms: 5x + -5x = 0 -4X + 0 = -4 + 12ahistwx + -5x -4X = -4 + 12ahistwx + -5x Divide each side by '-4'. X = 1 + -3ahistwx + 1.25x Simplifying X = 1 + -3ahistwx + 1.25x
| -3(x-9)-3(3x-5)-7x= | | 0.5(2x-6)+3=8(0.3x-5) | | 3v^2-1v=10 | | (13-2)2+(12-14*2)=a | | -9+5-3= | | 6y-8-3y+6=0 | | X^3-3x=1095 | | 2w-5=9(w-1) | | 11x-4=4(3x-2) | | xy-x^6y^6=0 | | 0.5x+2x+x+45=150 | | -5(r+9)=-96 | | 37.77=8g+3.85 | | 9x-7=23x-15 | | v+914=-21 | | 11x-4=4(3x+2) | | 15x-9-7=x+5 | | z+15+5z+9=180 | | 3x^2-2x-10=7 | | 6x+7+4x+5=90 | | 3X-16=2X+18 | | x^2+6x-8=3x-7 | | 4d-36-24d=2-16-4d | | 28=-4y+2(y+4) | | 6-2(x-2)=3(x+3)-9 | | 2d+15=27 | | x+5-3+3x-3x+x^2+4+x=35 | | 8c-c-1=9 | | 3(24-x)=6-x | | 14c-11=3(2c+7) | | 7=3-2+4x | | 6(w-2)+3w=24 |